'Tasks' appearing in primary school textbooks. (17th March 2018) - Butler, Yuko Goto; Kang, Katherine I; Kim, Heejin; Liu, Yeting
Abstract: The use of tasks has become increasingly popular in primary school English-as-a-foreign-language programmes. However, it remains unclear how appropriate the tasks introduced in textbooks are for young learners given their cognitive and linguistic developmental needs. To explore this issue, we analysed activities appearing in select government-approved textbooks (for grades 3–6) and teacher resource books in China and South Korea where task-based language teaching is being implemented by policy. We found that most activities would be classified as non-tasks according to the conceptualization of tasks in the field, but also that there were challenges in making such judgements due to some vagueness in these conceptualizations. Moreover, the tasks in the textbooks were differentiated across grade levels mainly through the manipulation of linguistic elements, but not of cognitive demands, resulting in fewer opportunities for meaningful target language use needed to stimulate children's language development. We offer suggestions for task design and curriculum development.